A New Analytical Model of the Brake Pad for Improved Calculation of the Centre of Pressure and Friction Coefficient in A Multi-Piston Disc Brake - Budinsky, Tomas; Brooks, Peter; Barton, David (International Journal of Engineering and Technology, 2018)
In recent experimental work it has been observed that the position of the centre of pressure (CoP) at the brake pad/disc interface has an influence on the onset of brake squeal. To determine the CoP during a braking event, a simple two-dimensional analytical model of the brake pad or more complex numerical finite element model of a disc brake are commonly used. This paper presents a new three-dimensional analytical model of a brake pad that determines the CoP position in both circumferential and radial directions. Due to higher complexity, this model provides more realistic clamp and friction force values, which can be used together with the more accurate radial position of the CoP for evaluation of the brake torque. The CoP position calculated using the new model was compared with the CoP evaluated by a finite-element model of an equivalent 8-piston opposed disc brake. The CoP results across the whole pad/disc interface showed a close correlation between these two approaches, giving the new analytical model a potential use in applications where an instantaneous value of the CoP with good accuracy is required. Finally, the new model was used to demonstrate possible improvement of the traditional method of the friction coefficient calculation. Due to greater accuracy the new model gives an approximately 8% larger value of the friction coefficient than the traditional approach.Â